Hubungan agama dengan modernisasi di Indonesia - Aulia, Habibah Shofi Futuhil (Maliki Interdisciplinary Journal, 2025)
Modernization as a process of social transformation has significantly influenced the dynamics of religiosity in Indonesia. In a rapidly evolving society, religion faces challenges such as rationalization, individualization, and shifts in values driven by technological advancement. This paper examines how religion responds to modernization through doctrinal adaptation, reform in religious education, digital media utilization, and the strengthening of women’s roles in religious spheres. The analysis employs grand, middle, and applied theoretical approaches to understand both structural and practical changes. The findings indicate that modernization does not diminish the role of religion but rather encourages its revitalization and reinterpretation to remain relevant in contemporary realities. This study affirms the importance of religious moderation as an integrative strategy for addressing societal transformation while preserving the core values of religious teachings.